Potret Peduli Lingkungan dalam Cerita Anak Mata: Di Tanah Melus karya Okky Madasari - Verga Dian Rasyiqah; Yenni Hayati (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
Ecocritic is the study of literature and the environment from an interdisciplinary point of view where all sciences come together to analyze the environment and provide possible solutions for the correction of contemporary environmental situations. Ecology is often found in adult literature, so eco-critical studies are rarely found in children's literature studies. Meanwhile, the values contained in ecology need to be instilled from an early age to create a generation that cares about the environment.This research discusses the form, background, and impact of caring for the environment in a short story of children's literature entitled Mata: Di Tanah Melus by Okky Mardasari. Data was collected using several techniques including reading and understanding, defining characters and identifying data related to research objectives. As for the research results where the background found is based on the creation of moral values towards environmental components. So that this form of caring for the environment has an impact on the related nation.